Paracrine Role of the Endothelium in Metabolic Homeostasis in Health and Nutrient Excess - Luk, Cheukyau; Haywood, Natalie J.; Bridge, Katherine I.; Kearney, Mark T. (Frontiers in Cardiovascular Medicine, 2022)
The vascular endothelium traditionally viewed as a simple physical barrier between the circulation and tissue is now well-established as a key organ mediating whole organism homeostasis by release of a portfolio of anti-inflammatory and pro-inflammatory vasoactive molecules. Healthy endothelium releases anti-inflammatory signaling molecules such as nitric oxide and prostacyclin; in contrast, diseased endothelium secretes pro-inflammatory signals such as reactive oxygen species, endothelin-1 and tumor necrosis factor-alpha (TNFα). Endothelial dysfunction, which has now been identified as a hallmark of different components of the cardiometabolic syndrome including obesity, type 2 diabetes and hypertension, initiates and drives the progression of tissue damage in these disorders. Recently it has become apparent that, in addition to vasoactive molecules, the vascular endothelium has the potential to secrete a diverse range of small molecules and proteins mediating metabolic processes in adipose tissue (AT), liver, skeletal muscle and the pancreas. AT plays a pivotal role in orchestrating whole-body energy homeostasis and AT dysfunction, characterized by local and systemic inflammation, is central to the metabolic complications of obesity. Thus, understanding and targeting the crosstalk between the endothelium and AT may generate novel therapeutic opportunities for the cardiometabolic syndrome. Here, we provide an overview of the role of the endothelial secretome in controlling the function of AT. The endothelial-derived metabolic regulatory factors are grouped and discussed based on their physical properties and their downstream signaling effects. In addition, we focus on the therapeutic potential of these regulatory factors in treating cardiometabolic syndrome, and discuss areas of future study of potential translatable and clinical significance. The vascular endothelium is emerging as an important paracrine/endocrine organ that secretes regulatory factors in response to nutritional and environmental cues. Endothelial dysfunction may result in imbalanced secretion of these regulatory factors and contribute to the progression of AT and whole body metabolic dysfunction. As the vascular endothelium is the first responder to local nutritional changes and adipocyte-derived signals, future work elucidating the changes in the endothelial secretome is crucial to improve our understanding of the pathophysiology of cardiometabolic disease, and in aiding our development of new therapeutic strategies to treat and prevent cardiometabolic syndrome.